The Minimally Invasive Star-Shaped Incision Technique and the Linear Incision Technique With Tissue Preservation for Percutaneous Bone Conduction Devices: A Retrospective Cohort Study - Strijbos, Ruben M.; Salameh, Samer; Bezdjian, Aren; Daniel, Sam J.; Thomeer, Hans GXM. (Frontiers in Surgery, 2022)
Purpose: To compare intra- and post-operative outcomes between the standard linear incision technique with tissue preservation (LITT-P) and the minimally invasive star-shaped incision (SSI). Study Design: A retrospective cohort study. Methods: Primary outcomes evaluated operative time, implant survival and intra-operative complications. Secondary outcome evaluated soft tissue tolerability assessed by the Holger’s classification. Results: A total of 38 implants were placed (19 LITT-P; 19 SSI). The median and mean surgical duration for the LITT-P group was statistically shorter than the SSI group (p = .0001). No intra-operative complications were reported for both surgical approaches. Five implants were lost during post-operative follow-up: one in the LITT-P and four in the SSI cohort. Both cohorts showed favourable soft tissue tolerability. Less Holgers 1 and 2 and more Holgers 3 soft tissue reactions were observed after the LITT-P compared to the SSI. Conclusion: The novel SSI approach could be an alternative option based on the theoretical benefits and found favourable (and similar) soft tissue outcomes. Implant loss and surgical time are aspects to investigate regarding long-term durability and warrant further research. Keywords: bone anchored hearing implant, BAHA, bone conduction, star-shaped incision, linear incision.